2017
DOI: 10.1002/cpe.4249
|View full text |Cite
|
Sign up to set email alerts
|

Novel efficient particle swarm optimization algorithms for solving QoS‐demanded bag‐of‐tasks scheduling problems with profit maximization on hybrid clouds

Abstract: SummaryUsers are willing to execute bag‐of‐task applications consisting of multiple tasks on clouds, since cloud resources are delivered in a pay‐as‐you‐go manner. Given multiple bag‐of‐task applications to be executed with user‐specified quality‐of‐service demands, a cloud provider has to outsource some tasks to public clouds when its private cloud has insufficient resources to afford all applications' tasks. The key issue is how to schedule tasks on hybrid clouds (environments consisting of a private cloud a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Abdi et al [28] considered BoT scheduling on a hybrid cloud platform and employed CPLEX solver to solve the problem. The authors in [29] and [30] employed particle swarm optimization algorithms to schedule BoT applications on hybrid clouds under deadline constraints.…”
Section: Related Workmentioning
confidence: 99%
“…Abdi et al [28] considered BoT scheduling on a hybrid cloud platform and employed CPLEX solver to solve the problem. The authors in [29] and [30] employed particle swarm optimization algorithms to schedule BoT applications on hybrid clouds under deadline constraints.…”
Section: Related Workmentioning
confidence: 99%
“…Service guarantees on hybrid clouds are much more complicated than single cloud. More research on data center performance optimization problems can be found in [12] and [32]- [34].…”
Section: B In Terms Of the Qosmentioning
confidence: 99%
“…A service level agreement (SLA) is a mutually agreed agreement between service providers and users to guarantee the performance and availability of services under certain overhead. Usually this overhead is a major factor to drive cloud providers to provide the QoS [8], [11], [12]. The optimal operating state of a service with a clear SLA is: adding additional resources to improve the system brings less revenue than the benefits of investing the resource in other services.…”
Section: Introduction a Motivationmentioning
confidence: 99%
“…The CPLEX was used to solve the problem with the results showing that the cloud federations benefit customers, compared with single cloud provider. Different from the three aforementioned works assuming that each task can be executed in an instance of any VM type, [29,30] considered computation-intensive BTSP with resource demands and deadline constraints on hybrid clouds from the perspective of cloud providers with an objective of maximizing profit. Both papers employed Particle Swarm Optimization algorithms to solve the considered problems.…”
Section: Related Workmentioning
confidence: 99%